Dataset on the prognostic value of cardiac biomarkers used in clinical routine in patients with severe aortic stenosis undergoing valve replacement - Barbieri, Fabian (Data Brief, 2020)
Hereby, the supplemental data of the research article “Long-Term Prognostic Value of High-Sensitivity Troponin T added to N-Terminal Pro Brain Natriuretic Peptide Plasma Levels before Valve Replacement for Severe Aortic Stenosis” are presented [1]. It offers enhanced input on the predictive value of these biomarkers considering the influence of the presence of concomitant coronary artery disease (CAD) in various severities as well as an additional cox proportional hazard model on cardiovascular mortality. Furthermore, the receiver operating characteristic (ROC) curves are shown as figures. The material described increases therefore the understanding of the predictive value of these already routinely available biomarkers and reduces the risk of potential bias due to possible confounding factors. It also underlines the urge for a multi-factorial approach in diagnostics to detect the optimal point for referral to valve replacement other than just symptomatic status, an observed reduction in left ventricular ejection fraction or the presence of CAD with the necessity for coronary artery bypass grafting (CABG) [2]. The data of the 3595 patients were gathered retrospectively at a consortium of four university hospital centers in Austria and combined with prospectively collected data on cardiovascular and all-cause mortality.